A pilot-scale study on the start-up of partial nitrification-anammox process for anaerobic sludge digester liquor treatment. (October 2017) - Wang, Gang; Xu, Xiaochen; Zhou, Liang; Wang, Chao; Yang, Fenglin
Highlights: A PN/A reactor for treating sludge digester liquor was started up successfully. FA (0.7–8.4 mg/L) and FAN (0.02–1.0 mg/L) resulted in a stable PN process. The fast reactivation and start-up of anammox was realized by adding hydroxylamine. Morphological properties and heme c content reflected the activity of anammox. The dominant anammox bacteria were associated with the genus Candidatus Brocadia . Abstract: Treatment of sludge digester liquor was successfully accomplished using a pilot-scale partial nitrification-anammox (PN/A) reactor with a nitrogen removal rate (NRR) of 1.23 kg N/m 3 /d. A stable and efficient PN process was attained by controlling the concentration of free ammonia (0.7–8.4 mg/L) and free nitrous acid (0.02–1.0 mg/L). The application of hydroxylamine played a vital role in the reactivation of anammox bacteria. The bacteria exhibited improved granule properties at a specific input power between 0.065 and 0.097 kW/m 3, and achieved a specific anammox activity (SAA) of 1.01 kg N/kg VSS/d on day 148. From day 0 to 120, the heme c content in the granules increased from 0.42 ± 0.1 to 5.77 ± 1.0 µmol/g VSS, with a corresponding increase in NRRs and SAAs. High-throughput sequencing techniques revealed that the dominant anammox bacterial genus was Candidatus Brocadia . These conclusions provide valuable information for the full-scale treatment of sludge digester liquor.